2020
DOI: 10.1186/s13568-020-01135-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broussonetia papyrifera silage on the serum indicators, hindgut parameters and fecal bacterial community of Holstein heifers

Abstract: This study investigated the effects of substitution of whole corn silage (WCS) with Broussonetia papyrifera silage (BPS) in different ratios on the serum indicators, hindgut fermentation parameters (pH, ammoniacal nitrogen, and volatile fatty acids), and fecal bacterial community of Holstein heifers. Sixteen heifers (8-month-old, 220 ± 30 kg) were randomly divided into four treatments according to different BPS substitution ratios of feed basis (0%, 25%, 50%, and 75%). The experiment consisted of a 7-day preli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Succinivibrio is abundant in the rumen of high-yielding and multi-product dairy cows, and its growth is related to the activities of urease, glutamine synthase, glutamate dehydrogenase, and glutamate synthase, which can improve nitrogen utilization (Hailemariam et al, 2020 ). Studies have shown that the abundance of the Rikenellaceae RC9 gut group is negatively correlated with diarrhea rate and positively correlated with nutrient digestibility, similar to the results of this experiment (Tian et al, 2020 ). Roseburia is a saccharolytic, butyrate-producing bacterium from human feces that can decompose a variety of sugars (e.g., xylose, galactose, raffinose, maltose, cellobiose, sucrose, and starch), and also affects the activities of β-glucuronidase and β-glucosidase in in vitro experiments, which is conducive to improve feed utilization (Machiels et al, 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…Succinivibrio is abundant in the rumen of high-yielding and multi-product dairy cows, and its growth is related to the activities of urease, glutamine synthase, glutamate dehydrogenase, and glutamate synthase, which can improve nitrogen utilization (Hailemariam et al, 2020 ). Studies have shown that the abundance of the Rikenellaceae RC9 gut group is negatively correlated with diarrhea rate and positively correlated with nutrient digestibility, similar to the results of this experiment (Tian et al, 2020 ). Roseburia is a saccharolytic, butyrate-producing bacterium from human feces that can decompose a variety of sugars (e.g., xylose, galactose, raffinose, maltose, cellobiose, sucrose, and starch), and also affects the activities of β-glucuronidase and β-glucosidase in in vitro experiments, which is conducive to improve feed utilization (Machiels et al, 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…The dominant species in the NG and CS materials was M. trichothecenolyticum , a Gram-positive and aerobic or weakly anaerobic non-spore-producing and acid-fast species. In contrast, the abundance of L. plantarum was low in all materials, indicating that WP were similar to forage and crop by-products; WP typically have a low abundance of LAB but a high abundance of undesirable bacteria before ensiling ( Tian et al, 2020 ; Du et al, 2021b ). Therefore, measures to control the microbial community are needed to improve silage fermentation.…”
Section: Discussionmentioning
confidence: 90%
“…S 10 b-c). For the families Christensenellaceae and Ruminococcaceae , which contain certain beneficial bacteria [ 40 44 ], the means of relative abundance in the LD group and HD group were increased by 89.57%, 110.27% and 804.9%, 21.59%, respectively, compared with the control group (Fig. S 11 ).…”
Section: Resultsmentioning
confidence: 99%